2000
DOI: 10.1021/ma992025s
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Unwinding of Polyelectrolytes under Stretching

Abstract: We consider the unwinding of a tethered, flexible, and weakly charged polyelectrolyte in a salt-free poor solvent under an externally imposed strain. Using scaling arguments, we predict that the restoring force of a stretched polyelectrolyte shows a sawtooth pattern as a function of the externally imposed end-to-end distance. This nonmonotonic behavior arises from a cascade of conformational transitions between necklace-like structures with different number of beads. The transitions result from the interplay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 41 publications
9
52
0
Order By: Relevance
“…(70) and (G15). We should mention, however, that explicit analytical comparison in the exactly solvable planar case 27 does not show any improvement of the agreement between the nonlinear and linearized equations with the inclusion of the quadratic contribution to the average densities. Any numerical indications in this direction, which were indeed observed in the planar case, 27 are purely fortuitous.…”
Section: G Legendre Transformation At the Linearized Levelmentioning
confidence: 81%
See 1 more Smart Citation
“…(70) and (G15). We should mention, however, that explicit analytical comparison in the exactly solvable planar case 27 does not show any improvement of the agreement between the nonlinear and linearized equations with the inclusion of the quadratic contribution to the average densities. Any numerical indications in this direction, which were indeed observed in the planar case, 27 are purely fortuitous.…”
Section: G Legendre Transformation At the Linearized Levelmentioning
confidence: 81%
“…This can be seen most clearly in the analytically tractable case of two infinite charged planes in electrochemical equilibrium with an infinite salt reservoir, which we present in a companion paper. 27 To avoid confusion we should stress at this point the exactness of the PB nonlinear solution at the mean-field level, its range of validity and limitations. In this work we discussed the linearization procedure in the framework of the nonlinear PB and the WS-cell model.…”
Section: Discussionmentioning
confidence: 99%
“…The PB equation [48] can be derived from a mean-field free energy functional [49,50,51,52,53,54] which itself is obtained from the underlying Hamiltonian either (i) as the saddle point of the field theoretic action [55,56,57,58], (ii) as a density functional reformulation of the partition function combined with a first order cumulant expansion of the correlation term [59], or (iii) from the Gibbs-Bogoljubov inequality applied to a trial product state [53]. The PB approximation gives a good description in the limit of high temperature and/or small charge densities (weak-coupling limit) when the microionic correlations that are neglected at the mean-field level are unimportant.…”
Section: Simulation Techniquementioning
confidence: 99%
“…The interesting thing is that the force is already zero even before the two strands are completely unzipped. This corresponds to the unraveling transition in the case of polymer in the condensed globule state being pulled by an external force [49][50][51][52]. There it was shown that for a polymer chain with N monomers, the number of monomers remaining in the globule state at the transition is still large and goes as N-n max ∼ N 3/4 [49].…”
Section: Unzipping Dna From a Condensed Globule State At Constanmentioning
confidence: 99%